ENHANCING PRODUCT CREATIVE AND INNOVATION THROUGH ADAPTIVE CAPABILITY: A LEARNING ORGANIZATION THEORY PERSPECTIVE - wibisono, dimas; Syafi'ah Wijayanti, Farah Nur; Lestari, Elisa Jayanti (Sekolah tinggi ilmu ekonomi pemuda, 2024)
Adaptability and innovation are crucial for company success in today's competitive global era. This research indicates that creativity and adaptive capability are essential components for driving product innovation. The methodology employed is quantitative research with a survey and non-probability sampling, involving 150 participants through purposive sampling. Data analysis was conducted using Smart-PLS 3.0. The study results show that creativity enhances organizational flexibility and responsiveness, enabling effective responses to market changes and challenges. Explicit knowledge, team dynamics, and a supportive work environment are proven to contribute to more adaptive and innovative products. Therefore, to achieve optimal innovation outcomes, organizations should focus on creating an environment that supports creativity and adaptive capability. This study underscores that the combination of creativity and adaptability enables companies to remain relevant and competitive. Managers and leaders must recognize the importance of investing in programs that enhance both aspects for long-term success. However, it should be noted that the findings of this study might be specific to certain industries or regions and may not necessarily be generalized to all types of companies or global markets.